Lesiones en Mus musculus inoculados con Mycobacterium phlei, Mycobacterium kansasii y Mycobcterium fortuitum aislados de suelos pampeanos (República Argentina) - Oriani, D.S. (2007)
The study objective was to determine the capacity of originate macroscopic and microscopic lesions of nine atypical mycobacteria inoculated in albino rats. The mycobacteria were isolated from farms soil samples at different places from La Pampa province (Argentina). It was investigated the three most frequent species (M. fortuitum, M. phlei and M. kansasii). The animals were endovenously inoculated with 1 mg of bacteria/ml-1 of fresh culture and kept in a restricted area during 60 days. After euthanasia, samples from different organs, for bacteriologic and histopathologic studies, were collected. M. phlei and M. kansasii showed lesions resemble to that produced by M. tuberculosis or M. bovis, whereas M. fortuitum did not show lesions in the animal model descript in this study. It is necessary to value other atypical mycobacterium isolated from soil and other inoculation ways in order to assist in clarifying the differential diagnosis in tuberculosis and other granulomatose diseases.